Synthesis of spiro[isoindole-1,5’-isoxazolidin]-3(2H)-ones as potential inhibitors of the MDM2-p53 interaction - Giofrè, Salvatore V.; Cirmi, Santa; Mancuso, Raffaella; Nicolò, Francesco; Lanza, Giuseppe; Legnani, Laura; Campisi, Agata; Chiacchio, Maria A.; Navarra, Michele; Gabriele, Bartolo; Romeo, Roberto (Beilstein Journal of Organic Chemistry, 2016)
A series of spiro[isoindole-1,5-isoxazolidin]-3(2H)-ones has been synthesized by 1,3-dipolar cycloaddition of N-benzylnitrone with isoindolin-3-methylene-1-ones. The regio- and stereoselectivity of the process have been rationalized by computational methods. The obtained compounds show cytotoxic properties and antiproliferative activity in the range of 9–22 μM. Biological tests suggest that the antitumor activity could be linked to the inhibition of the protein–protein p53-MDM2 interaction. Docking measurements support the biological data.
Keywords: antitumor agents; DFT studies; 1,3-dipolar cycloaddition; docking studies; spiro-compounds